The Current State of Democracy and Democratic Governance in Mongolia - Khatanbold, O (Mongolian Journal of International Affairs, 2013)
The paper aimed to express that democracy development and promoting democratic governance in Mongolia brought specific changes; however, difficulties and challenges. These are the process to institutionalize democracy, mainly in creating a democratic mechanism within public institutions. Failed policies, emphasis in political parties, and the election process influence democratic institution building. While the Mongolia’s democratic governance indicators initiative was very much owned by national stakeholders, an important aspect of the process was to engage with key international partners who specialize on democracy assessments. The nationally owned democratic governance indicators express multifaceted and intricate manifestations of social life, it is difficult to fully assess, and using this simplified assessment method. The content of paper has categorized by the survey data and information such conducted by the 2009-2010 on the “Changes in the state of Mongolia’s democratic governance: 2009-2010” and other initial sources in related to the democratic governance and democracy changes in Mongolia in that years. DOI: http://dx.doi.org/10.5564/mjia.v0i18.71 Mongolian Journal of International Affairs No.18 2013: 69-93